(untitled) (CIPEEX, 2025)
AgroAssist, as the name suggests, is an application designed to assist agricultural producers of micro, small, and medium scale, aiding in the process, progress, and development of crops. The app provides features such as location data to understand the climate and type of terrain in a given area, recommending the best vegetables and fruit trees, as certain plants are not suitable for specific areas. Users can take photos of their progress to document moments and actual development. With this information, users can select the desired crop and start planting, receiving recommendations for inputs (fertilizers), with a focus on organic cultivation for small-scale production. For medium-scale production, agricultural pesticides may be recommended for better control. The app will provide information on the water requirements of plants with reminders for irrigation. It will also offer tips periodically or at a set frequency through notifications, avoiding long texts that may not be read by users. If users have questions about planting or any other topic, they can use the chat feature for the specific plant, and other users can respond to their inquiries. Finally, there will be an image representing the plant’s development, allowing users to check if it meets expectations, enhancing their engagement with the app. The goal of AgroAssist is to make agriculture easier, contributing to the reduction of hunger and promoting greater contact with nature, which has numerous physical and mental benefits.